Health Care Associated Multidrug Resistant Acinetobacter Infections in a Tertiary Critical Care Center of Dhaka, Bangladesh - Mia, Md Faruk; Khan, Arif Ahmed; Chakraborty, Anjana (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Introduction: Acinetobacter spp, emerged as important pathogen exhibiting increasing antimicrobial resistance. Worldwide, multi-drug resistant Acinetobacter is being established as a significant cause of health-care-associated infections along with their resistant trait. Methods:This retrospective, cross-sectional study was done in critical care centers (CCC) of Combined Military Hospital (CMH) from May to September 2016. Total 69 patients with infection by Acinetobacter were included in this study. Center for Disease Control (CDC) criteria for selection of nosocomial infection were used. Specimen were inoculated in blood and MacConkey agar, incubated 24 hours at 37°C in aerobic condition and yield in plates were examined. Antibiotic resistance of isolated organisms were observed in Mueller Hinton agar sensitivity media by using Kirby Bauer disc diffusion method. Results:Among the total 69 (males 27, females 42,) and age range 2-75 years, Acinetobacter infected patients, 31 were from medical, 23 from surgical and 15 were from high dependency unit (HDU). Specimens were tracheal aspirate (24, 34.80%), urine (18, 26.90%), wound swab (12, 17.40%), pus (6, 8.70%), high vaginal swab (6, 8.70%) and bronchoalveolar lavage (3, 4.35%). Empiric antibiotics were given in all, one course of antibiotic was used in one, in others two or more courses were given. In the study, total 17 antibiotics were used for identifying resistance pattern of Acinetobacter isolates. Ceftazidime (91.30%), ceftriaxone (91.30%), amikacin(52.20%), gentamicin (33.33%), cotrimoxazole (50%) and ciprofloxacin (65.22%) were mostly resistant. Colistin appeared as most effective antibiotic with only 7.70% resistance rate. Conclusion: Acinetobacter, isolated in this study were resistant to most antibiotics. Colistin was the most sensitive one. Multi drug resistance (DR), extended DR and pan DR Acinetobacter organisms are reported worldwide, work on clinical presentation, trends of drug use in particular set up is important to combat the situation of ‘Going out of drug state’. J Bangladesh Coll Phys Surg 2020; 38(2): 59-63